From handmade to mass-produced and no way back? Globalisation, souvenirs and small business in Vanuatu. - Trupp, Alexander *; Shah, Chetan; Hitchcock, Michael (2023)
This study delves into the economic and sociocultural dimensions of the souvenir sector from the unique perspective of local market vendors in the South Pacific nation of Vanuatu. Findings reveal a heavy reliance on imported souvenirs, particularly for the cruise-ship market. Such practices often lead to the commodification and misrepresentation of local cultures and destinations, driven by the demands of tourists and the broader processes of international exchange and globalisation. By giving voice to grassroots producers and vendors within the handicrafts and souvenir sector, this research contributes to a more holistic understanding of the sector's dynamics and its role within the broader context of global tourism and economic change in emerging island economies.